2022
DOI: 10.1007/s10792-021-02162-9
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy in Greece: prevalence and risk factors studied in the medical retina clinic of a Greek tertiary hospital

Abstract: Purpose: To determine the prevalence of diabetic retinopathy (DR) and diabetic macular edema (DME) in a cohort of Greek diabetic patients and identify possible risk factors. Methods: Population-based, non-interventional, cross-sectional study of 300 diabetic Greek patients attending the medical retina clinics of a tertiary hospital. Clinical and imaging data were recorded and statistical analysis was performed. Con dence intervals (CI) at 95% and statistically signi cant p values ≤0.05 were set.Results: A tota… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The relationship between elevated blood lipid profiles and DR development of DR was complex. Previous studies on the correlation between conventional serum lipid levels (TG, TC, HDL-C, and LDL-C) and DR have shown conflicting results ( 10 , 13 , 19 , 37 ). Similarly, the current focus on the role of lipoprotein(a) in the pathogenesis of DR remains controversial ( 38 , 39 ).A recent study focused on the relationship between apolipoproteins and DR ( 40 ); however, these novel laboratory parameters have not yet been widely used in clinical practice.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The relationship between elevated blood lipid profiles and DR development of DR was complex. Previous studies on the correlation between conventional serum lipid levels (TG, TC, HDL-C, and LDL-C) and DR have shown conflicting results ( 10 , 13 , 19 , 37 ). Similarly, the current focus on the role of lipoprotein(a) in the pathogenesis of DR remains controversial ( 38 , 39 ).A recent study focused on the relationship between apolipoproteins and DR ( 40 ); however, these novel laboratory parameters have not yet been widely used in clinical practice.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies reported that common risk factors for DR included both duration of DM and age at visit ( 10 , 11 ); however, designing a prompt referral for DR screening should take into account the length of DM as a crucial determinant ( 4 , 13 ). A longer duration may represent a longer period of hyperglycemia-induced retinal toxicity, which is believed to be associated with both vascular and neural retinal death.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations